Sick building syndrome and its associated factors among adult people living in Hodan district Moqadishu Somalia - Yussuf, Saed M.; Dahir, Gallad; Salad, Abdi M.; Hayir T. M, Mohamud; Hassan, Shafie Abdulkadir; Gele, Abdi (Frontiers in Built Environment, 2023)
Background: Sick building syndrome (SBS) consists of a group of mucosal, skin, and general symptoms temporally that is related to residential buildings of unclear causes. Consequently, a cross-sectional study was carried out to identify the prevalence and contributing factors of SBS in adult people living in Hodan district, Mogadishu Somalia. Methods: A community based cross sectional study was conducted from September to October 2022 using a convenient sampling to include 261 individuals. The data was collected through structured questionnaire and an observational checklist. SBS was assessed using 15 building related symptoms and four socio-demographic characteristics. Five SBS conformation criteria were used. Descriptive statistics were presented, while bivariate and multivariate logistic regression analyses were conducted to assess the association between the dependent and independent variables. Results: The prevalence of SBS was 41% from the total of 261 participants. Based on the findings, SBS had a significant association with being female [AOR = 3.044, 95% CI = ((1.813, 5.110)], lack of functional windows [AOR = 3.543, 95% CI = (1.293, 9.710)], fungal growth in the buildings [AOR = 3.433, 95% CI = (1.223, 9.638)], recent use of pesticides, paints, and solvents[AOR = 2.541, 95% CI = (1.018, 6.343)], cooking inside building [AOR = 4.709, 95% CI = (1.469, 15.095)], outdoor air pollutant [AOR = 6.364, 95% CI = (2.387, 16.966)], use of charcoal for cooking [AOR = 1.846, 95% CI = (1.013, 3.365)], incensing habits of occupants [AOR = 4.375, 95% CI = (2.303, 8.308)] fan use [AOR = 2.067, 95% CI = (1.099, 3.886)] and dust in the living rooms [AOR = 5.151, 95% CI = (2.380, 11.152). Conclusion: SBS had a significant association with occupants’ sex, lack of functional windows, fungal growth in the buildings, recent use of pesticides, paints, and solvents, cooking inside the building, outdoor air pollutants, use of charcoal for cooking, incensing habits of occupants, and dust in the living rooms. High prevalence and poor understanding of sick building syndrome could threaten the health status of the occupants. Measures such as mass health education on identifiable risk factors should be taken to cope with these problems.